Pelayanan Penerbitan Surat Pernyataan Pelepasan Hak Atas Tanah (SPPHT) di Desa Motilango Kecamatan Tibawa Kabupaten Gorontalo - Abdullah, Nurlaelasari; Van Gobel, Lisda; Antu, Yahya (Innovative: Journal Of Social Science Research, 2024)
The aim of this research is to determine the Service for Issuing a Statement of Relinquishment of Land Rights (SPPHT) in Motilango Village, Tibawa District, Gorontalo Regency. This research uses a descriptive qualitative approach. Data collection was carried out through observation and interviews using interview guidelines submitted to a number of informants with the research focus, namely, SOP, Completion Time, and Responsiveness. The results of the research show that the Service for Issuing Statement of Relinquishment of Land Rights (SPPHT) in Motilango Village, Tibawa District, Gorontalo Regency from the aspects of standard operational procedures, completion time and responsiveness of the authorities is still less than optimal so that the people who come to handle it feel disadvantaged in terms of time and security. It is recommended that the Motilango village government, Tibawa subdistrict, Gorontalo district, improve its services to the community, especially in the Land Rights Release Statement Issuance Service (SPPHT) from the aspects of standard operational procedures, completion time and responsiveness so that the village government can provide maximum service to the community. Keywords: Publishing Services, Statement of Release of Rights Land